Crafting success inside the restaurant service Pre-WorldSkills Competition - Anuar, Jazira; Mahamed Ali, Faliza; Wan Kamarudin, Wan Nor Bayah; Samsudin, Azlina; Che Ngah, Haslina; Noorkhizan, Mohd Hazrin Iman; Zain, Razlan Adli; Adzmy, Azahar; Md Rus, Mohammad Hafizi; Deraman, Fauziah; Mat Ghani, Amanina; Rahmat, Norazlina; et al. (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
The Worldskills Competition (WSC) is widely regarded as the preeminent global platform for acknowledging and celebrating the exceptional talents and abilities of young individuals who have attained a remarkable degree of skill proficiency. The competition is accessible to all member nations of Worldskills International (WSI). Malaysia has been granted membership in the World Standards Institute (WSI) since 1993. Skills areas are assessed based on global norms of skill proficiency, covering 27 areas or fields from several backgrounds including restaurant services, bakery, patisserie & confectionary, additive manufacturing, cabinet making, heavy vehicle technology, car paintings, mobile robotics, prototype modelling, floristry, and electrical installation to name a few.